Covid-19, unequal economic recovery and maritime food trade - Maximilian Heigermoser; Thomas Glauben (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2021)
The Covid-19 pandemic poses unprecedented challenges to the global economy. While aggregated agricultural trade patterns remained largely unaffected by the pandemic, the World Bank still expects global poverty to rise for the first time in more than twenty years. Since late 2020, several developments have the potential to further jeopardize global food security. Precisely, sea freight rates for bulk carriers, which are primarily used in international agricultural trade, have surged to an eleven-year high. However, despite the significant role that transportation costs play in international food trade, current research tends to overlook the impact they have on trade flows and food price formation. Further, the Food Price Index provided by the Food and Agriculture Organization of the United Nations (FAO) has increased for eleven straight months, reaching a seven-year high. These developments constitute increased risk to food security, particularly in poorer regions. Only strengthened international cooperation and unrestricted trade can safeguard global food security in the coming phase of globally uneven economic recovery. Calls for domestic self-sufficiency, proposals to transition to an over-bureaucratized, command-and-control EU-food system, as well as tightening economic sanctions and countersanctions between leading economic powers endanger food security, especially in import-dependent regions. – – Die Covid-19-Pandemie stellt die Weltwirtschaft seit Anfang 2020 vor ungekannte, massive Herausforderungen. Zwar ließ der Weltagrarhandel insgesamt keine fundamentalen Verschiebungen gegenüber Vorjahren erkennen, dennoch geht die Weltbank in Folge der Pandemie vom ersten Anstieg globaler Armut seit über zwanzig Jahren aus. Seit Ende 2020 verstärken sich zudem Entwicklungen, die die globale Ernährungssicherheit weiter beeinträchtigen können. So stiegen Seefrachtraten für Massengutfrachter, die im internationalen Agrarhandel zuvorderst Verwendung finden, massiv an und befinden sich mittlerweile auf einem Elfjahreshoch. Während Transportkosten gerade im internationalen Handel mit Agrargütern eine beträchtliche Rolle spielen, wird ihr Einfluss auf Handelsströme und Preisbildung agrarischer Rohstoffe in der Forschung derzeit wenig untersucht. Seit Mitte 2020 lässt sich zudem eine kontinuierliche Aufwärtsbewegung des globalen Nahrungsmittelpreisindex der Food and Agriculture Organization of the United Nations (FAO) beobachten. Auch dieser hat mittlerweile ein Siebenjahreshoch erreicht. Entsprechend steht zu erwarten, dass sich das Risiko unzureichender Nahrungsmittelversorgung insbesondere in ärmeren Regionen einmal mehr erhöhen wird. Nur ein Mehr an internationaler Kooperation und uneingeschränktem Handel kann die globale Ernährungssicherheit in der kommenden Phase global ungleicher wirtschaftlicher Erholung sicherstellen. Rufe nach nationaler Selbstversorgung, oder gar überbürokratisierten und planwirtschaftlich anmutenden Agrarsystemänderungen, sowie sich verschärfende handelspolitische Sanktionsspiralen gefährden global gesehen die Ernährungssicherheit speziell importabhängiger Regionen.
urn:nbn:de:gbv:3:2-137521
Keywords: 330; Lebensmittelhandel; Frachtschifffahrt; Lebensmittelpreis; Ernährungssicherung; Coronavirus; Welt